2005
DOI: 10.1038/nature04020
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 demethylates repressive histone marks to promote androgen-receptor-dependent transcription

Abstract: Gene regulation in eukaryotes requires the coordinate interaction of chromatin-modulating proteins with specific transcription factors such as the androgen receptor. Gene activation and repression is specifically regulated by histone methylation status at distinct lysine residues. Here we show that lysine-specific demethylase 1 (LSD1; also known as BHC110) co-localizes with the androgen receptor in normal human prostate and prostate tumour. LSD1 interacts with androgen receptor in vitro and in vivo, and stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
1,536
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,545 publications
(1,606 citation statements)
references
References 16 publications
45
1,536
1
9
Order By: Relevance
“…Recent evidence demonstrates that LSD1 participates in androgen receptor (AR) and estrogen receptor-dependent gene expression. LSD1 is implicated in H3K9 demethylation associated with PSA gene activation in an AR-dependent manner [30], and with activation of most ERa gene targets in MCF7 cells [31]. In our study, we show by qRT-PCR and immunoblotting that LSD1 is expressed in Sertoli cells and is recruited in vivo at the ERE2/3 sites of the faah gene both in the presence and in the absence of the ligand.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Recent evidence demonstrates that LSD1 participates in androgen receptor (AR) and estrogen receptor-dependent gene expression. LSD1 is implicated in H3K9 demethylation associated with PSA gene activation in an AR-dependent manner [30], and with activation of most ERa gene targets in MCF7 cells [31]. In our study, we show by qRT-PCR and immunoblotting that LSD1 is expressed in Sertoli cells and is recruited in vivo at the ERE2/3 sites of the faah gene both in the presence and in the absence of the ligand.…”
Section: Discussionsupporting
confidence: 52%
“…LSD1 is an amine oxidase, and thus its activity can be inhibited by monoamine oxidase inhibitors like pargyline (Parg) [21,31]. We found that treatment with Parg, as well as knock-down of lsd1 gene in Sertoli cells transfected with Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…SUMO-3 can enhance AR transcriptional activity independent of its sumoylation activity (Zheng et al, 2006). LSD1 is a histone demethylase that recently was shown to act on the AR and be overexpressed in prostate cancer (Metzger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%